1991
DOI: 10.1055/s-0038-1634828
|View full text |Cite
|
Sign up to set email alerts
|

Record Linkage Strategies

Abstract: Record linkage techniques can help identify the same patient for matching diverse files (hospital discharge abstracts, insurance claims, registries, Vital Statistics data) which contain similar identifiers. Prior knowledge of whether a linkage is feasible is important to prevent wasted effort (additional data collection or data manipulation), which decreases the cost-effectiveness of the linkage. Using examples generated by linking the Manitoba Health Services Commission data with Vital Statistics files, a met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…33±35 High percentages of successful linkages, although not as high as in our study, have been reported. 34 Thus, register-based follow-up studies of this kind are also possible in the absence of a national or regional identification number system, but they are likely to be more difficult and expensive.…”
Section: Discussionmentioning
confidence: 99%
“…33±35 High percentages of successful linkages, although not as high as in our study, have been reported. 34 Thus, register-based follow-up studies of this kind are also possible in the absence of a national or regional identification number system, but they are likely to be more difficult and expensive.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, only Roos and Wajda [20] compare deterministic and probabilistic methods and make suggestions on when their use is appropriate. The literature appears to contain no studies that compare how the methods compare quantitatively when applied to common data sets.…”
Section: Introductionmentioning
confidence: 98%
“…Newcombe [17] contains valuable information for practitioners. Larsen and Rubin [18], Winkler [19], and Roos and Wajda [20] compare di erent linkage strategies.…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy of record linkage using probabilistic data matching is high with the percentage of true matches estimated to be 97-99 percent depending on the number of matching variables used [9]. Validation of the registers involved in the linkages has been published [1].…”
Section: Quality Controlmentioning
confidence: 99%